A Review of Inactive Materials and Components of Flexible Lithium‐Ion Batteries. (22nd September 2017) - Foreman, Evan; Zakri, Waleed; Hossein Sanatimoghaddam, Mohammad; Modjtahedi, Ali; Pathak, Saurabh; Kashkooli, Ali Ghorbani; Garafolo, Nicholas G.; Farhad, Siamak
Abstract: Flexible Li‐ion batteries (LIBs) have a strong oncoming consumer market demand for use in wearable electronics, flexible electronics, and implantable medical devices. This market demand necessitates research on flexible LIBs to fulfill the energy requirements of these devices. One of the main areas of research of flexible LIBs is the active and inactive materials used in manufacturing these batteries. Active materials are those used in the battery electrodes to store lithium in their structure. The remaining materials in flexible LIBs, which do not directly contribute to energy storage, are inactive materials. Inactive materials and components—including electrode conductive materials, binders, separator, current collectors, electrolyte, and casing/packaging—make up almost 60% of the total weight of a LIB. Thus, they are important in the determination of energy and power density of flexible LIBs. This study reviews the inactive materials and components of flexible LIBs from two aspects. First, inactive materials and components used in flexible LIBs and their properties are compared. Then, the compatibility and stability of inactive materials and components are discussed. Overall, this article gives an extensive insight to researchers on inactive materials and components employed so far for flexible LIBs. Abstract : Inactive components of a flexible lithium ion battery (LIB) consist of the components that do not directly contribute to energy storage. However, they play a significant role in determination of the battery energy and power density, cycle life, cost, and degree of flexibility. Inactive components of a LIB are electrode binder and conductive materials, electrolyte, current collectors, casing, and separator.